MELAWAN KORUPSI (BIOGRAFI POLITIK UMAR IBN ABD AL-AZIZ) - M. Abdul Karim (Millah: Journal of Religious Studies, 2007)
Umar ibn Abd al-Aziz was a great leader throughout Islamic History. He gave an outstanding role in Umayyad Dynasty. He was differ from some of his corrupted, unkind, and injustice predecessors. This Caliph which called, Umar the Second used to choose popular policy that touch the people around him. This legendary leader in Islamic History has many attractive historical evidences provoke researchers to make further studies about him. He based his policies on al-Qur’an and Sunnah. Umar II was caring and treating his people with just (justice), in another angle he also his strict forward attitude toward corrupted officials and those who violate Allah’s rules.This study reveilled variety of political decisions which was made by Umar ibn Abd al-Aziz during his leadership. Based on variety of sources, the article can find in political decisions of Umar II an example to be followed by moslem leaders nowadays and those who who are in the future as well.